2012
DOI: 10.1371/journal.pgen.1002765
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Differences in Genetic Susceptibility to IgA Nephropathy: GWAS Replication Study and Geospatial Risk Analysis

Abstract: IgA nephropathy (IgAN), major cause of kidney failure worldwide, is common in Asians, moderately prevalent in Europeans, and rare in Africans. It is not known if these differences represent variation in genes, environment, or ascertainment. In a recent GWAS, we localized five IgAN susceptibility loci on Chr.6p21 (HLA-DQB1/DRB1, PSMB9/TAP1, and DPA1/DPB2 loci), Chr.1q32 (CFHR3/R1 locus), and Chr.22q12 (HORMAD2 locus). These IgAN loci are associated with risk of other immune-mediated disorders such as type I dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
272
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 321 publications
(289 citation statements)
references
References 47 publications
15
272
0
2
Order By: Relevance
“…In a recent GWAS replication study, the association of 1q32 with IgAN susceptibility was confirmed in eight new independent cohorts. 29 On the basis of this genetic association, we further explored the clinical significance of rs6677604 in IgAN. Our finding that the rs6677604 locus was associated with mesangial C3 deposition in IgAN implied a functional role for rs6677604 in complement activation and more importantly, aroused our interest in the complement activation mechanism in IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent GWAS replication study, the association of 1q32 with IgAN susceptibility was confirmed in eight new independent cohorts. 29 On the basis of this genetic association, we further explored the clinical significance of rs6677604 in IgAN. Our finding that the rs6677604 locus was associated with mesangial C3 deposition in IgAN implied a functional role for rs6677604 in complement activation and more importantly, aroused our interest in the complement activation mechanism in IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…We manually curated a list of SNPs that both passed genome-wide significance and were associated with kidney disease traits (Table S7). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] To acquire independent loci, we removed any SNPs having r 2 R 0.2. In total, we analyzed 110 leading SNPs and 2,357 tagging SNPs with r 2 R 0.8 (Table S7).…”
Section: Kidney Eqtl Highlights the Genetics Of Disease Traitsmentioning
confidence: 99%
“…[5][6][7][8][9] The incidence of IgAN varies geographically, being most prevalent in East Asian populations and less prevalent in European and African populations. 10,11 Six genomewide association studies have collectively identified 20 distinct loci associated with IgAN. Interestingly, most of these loci are shared with other immune-related diseases.…”
mentioning
confidence: 99%